The interplay of inflammation and placenta in maternal diabetes: insights into Hofbauer cell expression patterns - Tauber, Zdenek; Burianova, Adela; Koubova, Katerina; Mrstik, Max; Jirkovska, Marie; Cizkova, Katerina (Frontiers in Immunology, 2024)
Inflammation of the placenta is harmful to both the fetus and the mother. Inflammation is strongly associated with diabetes, a common complication of pregnancy. Hofbauer cells (HBCs), unique immune system cells of fetal origin in the placenta, play complex roles, including growth of placental villi and their branching, stromal remodelling, and angiogenesis. Our study investigated the expression of IL-1β, IL-10, CYP2C8, CYP2C9, CYP2J2 and sEH in HBCs from patients with type 1 diabetes mellitus (T1DM) and gestational diabetes mellitus (GDM) compared to healthy controls using immunohistochemistry. We also assessed the structure of the villus stroma. In T1DM, HBCs showed inflammatory activation characterised by increased IL-1β and decreased CYP epoxygenase expression compared to normal placentas. Conversely, significant inflammation in HBCs appeared less likely in GDM, as levels of IL-1β and CYP epoxygenases remained stable compared to normal placentas. However, GDM showed a significant increase in sEH expression. Both types of diabetes showed delayed placental villous maturation and hypovascularisation, with GDM showing a more pronounced effect. These facts suggest an association of the CYP epoxygenase-EETs-sEH axis with IL-1β expression as well as villous stromal hypovascularisation. Given the stable high expression of IL-10 in both controls and both types of diabetes, it appears that immune tolerance is maintained in HBCs.However, the expression of IL-10 in HBCs does not reflect the overall immunological tolerance at the fetal-maternal interface, as other structures such as the trophoblast and maternal decidua contribute significantly.